Bimekizumab Sebagai Pengobatan Pilihan Psoriasis Vulgaris Tipe Plak - Jenifer Putri Sianto; Rompu Roger Aruan; Grace Pudjiadi Widodo; Arini Astari Widodo (Jurnal MedScientiae, 2023)
Psoriasis is a chronic inflammatory skin disease which is associated with genetic predisposition and autoimmune pathogenic traits. This disease is characterized with erythematous plaque and silvery scales that is severely itchy, swells, and is painful, which causes patients to have a poor quality of life. In the last years, there has been several effective therapies that is developed to treat psoriasis, but despite this, a proportion of patients do not respond or lose respond over time towards these therapies. However, there is a novel therapy found which is Bimekizumab, it is the first monoclonal antibody that is designed to target both IL-17A and IL-17F simultaneously. Bimekizumab is proved as the choice of therapy for psoriasis that reduces psoriasis plaque patients PASI score up to 100 with a minimal and mild side effects, and no immunogenicity detected. It also works in a shorter amount of time to reach PASI 90 as early as week 4 and can maintain response up to week 52. This objective of this literature review is to discuss about the superiority of bimekizumab compared to other therapies for psoriasis vulgaris.